Sevoflurane Post-conditioning Enhanced Hippocampal Neuron Resistance to Global Cerebral Ischemia Induced by Cardiac Arrest in Rats through PI3K/Akt Survival Pathway - Wang, Zhihua; Ye, Zhi; Huang, Guoqing; Wang, Na; Wang, E.; Guo, Qulian (Frontiers in Cellular Neuroscience, 2016)
The purpose of this current study is to evaluate whether improvement of mitochondrial dysfunction was involved in the therapeutic effect of sevoflurane postconditioning in global cerebral ischemia after cardiac arrest (CA) via the PI3K/Akt pathway. In the first experiment, animals were randomly divided into three groups: a sham group, a CA group, a CA+sevoflurane postconditioning group (CA+SE). Sevoflurane postconditioning was achieved by administration of 2.5% sevoflurane for 30 min after resuscitation. Sevoflurane postcontioning has a significant neuroprotective effect by increasing survival rates and reducing neuronal apoptosis. Additionally, the gene and protein expression of PGC-1α, NRF-1 and TFAM, the master regulators of mitochondrial biogenesis, were up-regulated in the CA+SE group, when compared to the CA group. Similarly, in contrast to the CA group, mitochondria-specific antioxidant enzymes, including heat-shock protein 60 (HSP60), peroxiredoxin 3 (Prx3) and thioredoxin 2 (Trx2)were also increased in the CA+SE group. Finally, administration of sevoflurane ameliorated mitochondrial reactive oxygen species (ROS) formation and maintained mitochondrial integrity. In the second experiment, we investigated the relationship between the PI3K/Akt pathway and mitochondrial biogenesis and mitochondria-specific antioxidant enzymes in sevoflurane-induced neuroprotection. The selective PI3K inhibitor wortmannin not only eliminated the beneficial biochemical processes of sevoflurane by reducing the level of mitochondrial biogenesis-related proteins and aggravating mitochondrial integrity, but also reversed the elevation of mitochondria-specific antioxidant enzymes induced by sevoflurane. Therefore, our data suggested that sevoflurane postconditioning provides neuroprotection via improving mitochondrial biogenesis and integrity, as well as increasing mitochondria-specific antioxidant enzymes by a mechanism involving the PI3K/Akt pathway.